2022
DOI: 10.4103/ijcm.ijcm_985_21
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Facility Delivery in the 12th District of Kandahar City, Kandahar, Afghanistan

Abstract: Background: Maternal mortality and morbidity are increasing public health concerns in Afghanistan. Even more worrying is maternal death due to causes that can be prevented through maternal healthcare services utilization during pregnancy and delivery. Objectives: We sought to investigate the magnitude of women giving birth in a health facility and its associated factors in the 12 th district of Kandahar city, Kandahar province, Afghanistan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
2
6
2
Order By: Relevance
“…In contrast to the current finding, a study among rural women of the Chandpur district of Bangladesh revealed that 74% of women delivered in a health facility. 12 Our study finding is also lower than several other studies conducted in a rural district in Nepal (55%), 16 rural Myanmar (54.7%), rural communities in Afghanistan (71.8%) 17 and rural communities in Ethiopia (58.17%). 18 That notwithstanding, our study finding is higher than a study conducted in rural communities in Eritrea 19 where researchers found that only 24.6% of women had institutional delivery.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…In contrast to the current finding, a study among rural women of the Chandpur district of Bangladesh revealed that 74% of women delivered in a health facility. 12 Our study finding is also lower than several other studies conducted in a rural district in Nepal (55%), 16 rural Myanmar (54.7%), rural communities in Afghanistan (71.8%) 17 and rural communities in Ethiopia (58.17%). 18 That notwithstanding, our study finding is higher than a study conducted in rural communities in Eritrea 19 where researchers found that only 24.6% of women had institutional delivery.…”
Section: Discussioncontrasting
confidence: 76%
“…The disparity in the findings of the current study and the other studies could be attributed to improved access to healthcare, increased awareness and other sociodemographic variations in these situations. 17 Despite several efforts by the government to improve health facility delivery, the rate among women in rural Bangladesh still remain low.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in line with the results of a systematic review undertaken in developing countries [ 50 ]. Other studies in Afghanistan have also highlighted the important role of husbands’ education in decision-making regarding seeking healthcare during pregnancy [ 21 , 51 ]. Consistent with previous studies, a husband with better education may have better understanding of the benefits of ANC services his wife would receive during ANC visits and such husbands are more likely to discuss with their spouses about issues related to women’s reproductive health and maternal health services [ 13 , 21 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, one study found that sociodemographic and cultural (woman’s role in making the decision to seek PNC service) factors were associated with the utilization of PNC visits [ 29 ]. Three studies reported that sociodemographic and cultural factors were associated with institutional deliveries or skilled birth attendance (SBA) deliveries [ 30 , 31 , 35 ]. One of the three studies reported that women who had at least four ANC visits were more likely to give birth in a health facility or with SBA than those who had none, and women from higher socioeconomic status used institutional deliveries more than women from lower socioeconomic status [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the three studies reported that women who had at least four ANC visits were more likely to give birth in a health facility or with SBA than those who had none, and women from higher socioeconomic status used institutional deliveries more than women from lower socioeconomic status [ 30 ]. The second study revealed that a history of complications in previous births, the husband’s education, and ANC visits were associated with institutional deliveries [ 31 ]. Another of the three aforementioned studies indicated that socioeconomic status and decisions made for women on where to deliver were correlated with SBA deliveries [ 35 ].…”
Section: Introductionmentioning
confidence: 99%